Greener and rapid magnetic solid phase microextraction method using Fe3O4@Al2O3/AC for chromatographic determination of neonicotinoid pesticides in vegetable oils - Musiiwa V. Sengane; Masixole Sihlahla; Philiswa N. Nomngongo; Nomvano Mketo (Advances in Sample Preparation)
A greener sample preparation method based on magnetic solid phase microextraction (MSPμE) was developed for the preconcentration of neonicotinoid pesticides (acetamiprid, imidacloprid, thiacloprid and thiamethoxam) in vegetable oil samples followed by separation and quantification using high performance liquid chromatography with diode array detector (HPLC-DAD). Different characterisation techniques such as Fourier Transform Infrared Spectroscopy (FTIR), Powder X-ray diffraction analysis (PXRD), Thermogravimetric Analysis (TGA), Transmission electron microscopy (TEM), and scanning electron microscope and energy-dispersive X-ray spectroscopy (SEM-EDS) confirmed the synthesised magnetic nano adsorbents (Fe3O4, Fe3O4@Al2O3 and Fe3O4@Al2O3/AC). The most influential parameters affecting MSPμE of NEOs by Fe3O4@Al2O3/AC were examined using a multivariate optimisation approach and 8 min extraction time, 13 pH, 9 mg adsorbent mass, and 0.5 mL eluent volume were optimal parameters. The proposed Fe3O4@Al2O3/AC method showed high accuracy (80–119.21%) and precision (≤10 %) for all the investigated NEOs. Additionally, the obtained limit of detection (LOD) ranged from 0.5–1.76 ng µL-1, the limit of quantification (LOQ) ranged from 1.87–6.62 ng µL-1 and satisfactory high preconcentration factors (73.02- 407.0) were comparable with literature reported studies. The Analytical GREEness calculator AGREE, BAGI and NEMI analysis confirmed greenness of MSPμE. After that, the validated MSPμE method was applied to real vegetable oil samples (avocado, canola, olive and sunflower), and fortunately, all the investigated NEOs were below LODs of the proposed MSPμE /HPLC-DAD methods.